A critical reappraisal of the treatment modalities of normal appearing thoracic aorta mural thrombi - Karaolanis, Georgios (Ann Transl Med, 2017)
Mural thrombus in non-atherosclerotic or aneurysmatic thoracic aorta is a relatively uncommon entity. Currently there is no consensus on the appropriate therapeutic algorithm of its management. We aim to present the current knowledge on the treatment of thoracic aorta mural thrombi (TAMT) in minimally atherosclerotic vessels and we hope that the juxtaposed discussions will shed light on the uncharted waters regarding this rare syndrome. The MEDLINE/PubMed database was searched for publications with the medical subject “aortic mural thrombus” and keywords “thoracic”, “embolism”, “normal vessel”, “minimally atherosclerotic vessel” or “treatment”. We restricted our search to English language, till January 2017. The electronic literature search yielded 23 reports that were deemed appropriate for further analysis. Anticoagulation is the standard of care for the treatment of the thrombus whereas surgical and interventional treatment seems to be related with increased mortality and lower recurrence rates. TAMT treatment is controversial. Anticoagulants are the mainstay of treatment but surgery seems to gain ground in several settings as an only therapy or a combined treatment modality. More data are needed on the role of novel oral anticoagulants and endografts.